Refinement of the Jensen Inequality for Convex Functions of Several Variables with Applications: Muhammad Adil Khan, Josip Pecaric - Team, Support (Thai Journal of Mathematics, 2022)
In this manuscript we give a refinement of Jensen's inequality for convex functions of several variables associated to certain tuples.As applications we deduce refinements of Beck's inequality. At the end of the manuscript further generalization has been presented for nfinite certain sequences.